2001
DOI: 10.1007/s001340101063
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive pressure support ventilation in patients with acute respiratory failure after bilateral lung transplantation

Abstract: NIV administration was well tolerated and avoided intubation in the large majority of patients (86%); in NIV responders the rate of complications was low and ICU mortality nil. NIV should be considered as an interesting alternative to conventional ventilation in patients who require ventilatory support after BLT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
6

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(33 citation statements)
references
References 0 publications
0
27
0
6
Order By: Relevance
“…Several studies looked at the use of NIV after lung surgery [64][65][66]. AURIANT et al [64] conducted a randomised controlled trial in patients who experienced respiratory distress after lung resection.…”
Section: Immunosuppressed Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies looked at the use of NIV after lung surgery [64][65][66]. AURIANT et al [64] conducted a randomised controlled trial in patients who experienced respiratory distress after lung resection.…”
Section: Immunosuppressed Patientsmentioning
confidence: 99%
“…A reduction in ETI rate and a clear benefit in terms of hospital survival was observed with NIV. A noncontrolled study suggested interesting results using NIV after bilateral lung transplantation [65].…”
Section: Immunosuppressed Patientsmentioning
confidence: 99%
“…This aspect increased the interest for the application of NIV techniques, which seem able to decrease the rate of nosocomial infectious complications, with a similar level of efficacy in terms of gas exchanges improvement and patients acceptation. In a recent prospective nonrandomised study ROCCO et al [26] evaluated the role of NIV in a group of 21 patients developing ARF after bilateral lung transplantation. All the patients received noninvasive pressure support ventilation (NIPSV) through a face mask.…”
Section: Noninvasive Ventilation In the Treatment Of Hypoxaemic Acutementioning
confidence: 99%
“…Eighteen patients (86%) avoided intubation. No patient treated successfully with NIV died [26]. ANTONELLI et al [23] conducted a randomised study to compare NIV delivered through a face mask to standard treatment with supplemental oxygen administration as a modality to avoid ETI in 40 solid organ transplant recipients with acute hypoxaemic respiratory failure.…”
Section: Noninvasive Ventilation In the Treatment Of Hypoxaemic Acutementioning
confidence: 99%
“…More recently, some papers have suggested that NIV can be successfully used in other conditions, such as ARF in immunocompromised patients, pulmomary oedema and after bilateral lung transplantation [34][35][36][37]. The confirmation of such data through the use of NIV on a higher number of patients will widen the field of application of NIV and, consequently, create the need to implement RICUs.…”
Section: Discussionmentioning
confidence: 99%